Citizenship education: Foundations of Indonesian nationalism and democracy - Dadang Mulyana (Journal Of Data Science, 2024)
Nationalism and democracy are two crucial aspects in building a strong and sovereign country. Citizenship education has the potential to become the main means of forming nationalist awareness and strengthening democratic values among Indonesian society. This research aims to examine the role of citizenship education in building the foundations of nationalism and democracy in Indonesia. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of citizenship education has a significant impact in forming nationalist awareness and democratic participation among Indonesia's young generation. Respondents stated that through PKN learning, they better understand the values of Pancasila, their rights and obligations as citizens, as well as the importance of participation in political and social life. These results confirm that citizenship education plays an important role in forming strong national character and identity and improving the quality of participation in democracy, which is a crucial aspect in building a sovereign and just nation.